The role of country origin and product involvement in effecting consumers' product preference for imported products: from the perspective of Kuching Urban city consumers - Phang, Joseph Siew Guan (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The purpose of this study was to examine the COO effect in the consumer behavior of Kuching urban city. This study is aimed to examine how COO affects product preference of consumers in Kuching urban city. Apart from that, it is also the objective of this study to examine how the effect of COO varies across high and low involvement products from different country of origin. For further study, the effect of COO on consumers' perception towards price and quality of products was also examine. It was found that Kuching consumers generally prefer products from more developed countries such as Japan to products from less developed country such as China. It was also found that Kuching consumers perceive products from more developed countries to be higher in quality and price, while products from less developed countries to be lower in terms of both quality and price.